Synthesis, morphology and thermal properties of the POSS-containing polyurethane nanocomposites - L. V. Karabanova; L. A. Honcharova; V. I. Sapsay; D. O. Klymchuk (Хімія, фізика та технологія поверхні)
A series of nanocomposites based on polyurethane matrix (PU) have been synthesized using 1,2-propanediolisobutyl polyhedral oligomeric silsesquioxanes (POSS) as functionalized nanofiller. The effect of POSS content (0–10% by weight) on the structure and properties of the created nanocomposites have been investigated. The polymer matrix (PU network) was synthesized from adduct of  trimethylolpropane (TMP) and toluene 2,4-diisocyanate (TDI), and oligoetherglycol with Mw = 5000 g/mol-1. FTIR analysis was used for investigation of 1,2-propanediolisobutyl-POSS incorporation possibility into PU matrix. The FTIR spectra of neat POSS, neat TDI-TMP adduct and model system adduct+POSS before curing and after curing were analyzed. The FTIR-ATR data obtained evidence that the POSS structure is chemically incorporated into the PU matrix during process of nanocomposites preparation. The thermal behaviour of POSS-containing nanocomposites by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) was investigated. From the DSC data the glass transition temperature (Tg) of the nanocomposites was found to be increased with increasing of POSS content. Overall the results of thermal properties investigation of POSS-containing nanocomposites demonstrate that the created nanocomposites are significantly more thermally stable in compare with native matrix. The morphology of POSS-containing nanocomposites by SEM was analyzed. The incorporation of the POSS nanoparticles into PU matrix was found results in the formation of more ordered structure. Consequently the POSS introduced into PU matrix acts as nanostructuring agent. As a result the nanocomposites with more ordered structure are formed, so leading to obtaining of materials with improved thermal stability.